Perencanaan Penjadwalan Preventive Maintenance Mesin Pounch dengan Critical Path Method di PT. Grafika Nusantara - Yuli Setiawannie; Nita Marikena (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Maintenance is one of the main activities in the manufacturing sector that greatly affects the quality and quantity of production, production costs, and customer satisfaction. Thus, it is necessary to plan a preventive maintenance schedule to maintain the condition of the machine so that the production process runs optimally. PT. Grafika Nusantara is a paper management industry company specializing in continuous form, printing, and office stationery, whose production process runs continuously. In the production process, the company often has problems with the punch machine, which is one of the machines in the factory as a printer for paper into envelopes. The problem is due to lack of supervision and maintenance on the punch machine by the company can result in the machine being damaged and the production target not being achieved. The objective of this paper is to plan preventive maintenance scheduling on the punch machine with the Critical Path Method (CPM) and to determine the cost of preventive maintenance for 1 year. The results that can be concluded in this study are that the maintenance scheduling of the punch machine with the CPM method can save maintenance time, which is 30 hours and the cost of preventive maintenance for 1 year is Rp. 1,400,000.